Adjustment to target debt maturity and equity mispricing: evidence from Asia Pacific - Kamarudin, Fakarudin; H. I., Hussain; A. R. A., Hadi; A., Mohamed Isa; M. A., Salem; N. H., Jabarullah (Czestochowa University of Technology, 2018)
This paper examines firms’ target adjustment behavior for debt maturity structure for selected countries from the Asia Pacific region. The literature documents that managers’ structure debt issues in line with a target maturity structure which is limited by transactions costs, information asymmetry, agency problems, liquidity needs as well as institutional factors. Our paper contends that firms adjust to target levels at differing rates based on whether the current maturity structure is above or below target levels as well as equity mispricing. We estimate the target debt maturity based on the lead level and measure speed of adjustment to target levels by regressing the difference between the simulated and actual values. Our findings indicate that firms which are below target debt maturity tend to adjust at more rapid rates during periods of overvaluation. Firms which are above target debt maturity tend to adjust at more rapid rates during periods of undervaluation. Our findings indicate asymmetric adjustment rates indicating that debt maturity structure serves as an important tool for signaling. The implications provide a better understanding on the impact of debt maturity on information asymmetry leading to differences in adjustment to target debt maturity structures.